Doxorubicin-Conjugated Nanoparticles for Potential Use as Drug Delivery Systems - Alua Imantay; Nariman Mashurov; Balnur A. Zhaisanbayeva; Ellina A. Mun (Nanomaterials)
Doxorubicin (DOX) is one of the most widely used chemotherapy drugs in the treatment of both solid and liquid tumors in patients of all age groups. However, it is likely to produce several side effects that include doxorubicin cardiomyopathy. Nanoparticles (NPs) can offer targeted delivery and release of the drug, potentially increasing treatment efficiency and alleviating side effects. This makes them a viable vector for novel drug delivery systems. Currently, DOX is commonly conjugated to NPs by non-covalent conjugation–physical entrapping of the drug using electrostatic interactions, van der Waals forces, or hydrogen bonding. The reported downside of these methods is that they provide a low drug loading capacity and a higher drug leakage possibility. In comparison to this, the covalent conjugation of DOX via amide (typically formed by coupling carboxyl groups on DOX with amine groups on the nanoparticle or a linker, often facilitated by carbodiimide reagents), hydrazone (which results from the reaction between hydrazines and carbonyl groups, offering pH-sensitive cleavage for controlled release), or disulfide bonds (formed through the oxidation of thiol groups and cleavable by intracellular reducing agents such as glutathione) is more promising as it offers greater bonding strength. This review covers the covalent conjugation of DOX to three different types of NPs—metallic, silica/organosilica, and polymeric—including their corresponding release rates and mechanisms.